2006
DOI: 10.1161/01.res.0000238387.85144.92
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cell Cycle Regulatory and Inflammatory Genes As Predominant Targets of p38 Mitogen-Activated Protein Kinase in the Heart

Abstract: Abstract-Mitogen-activated protein kinases (MAPKs) regulate cardiomyocyte growth and apoptosis in response to extracellular stimulation, but the downstream effectors that mediate their pathophysiological effects remain poorly understood. We determined the targets and role of p38 MAPK in the heart in vivo by using local adenovirus-mediated gene transfer of constitutively active upstream kinase mitogen-activated protein kinase kinase 3b (MKK3bE) and wild-type p38␣ in rats. DNA microarray analysis of animals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 35 publications
(33 reference statements)
7
84
0
Order By: Relevance
“…Activation of p38 by TAK1 induced ventricular hypertrophy [41]. Tenhunen et al [42] injected adenovirus encoding wild-type p38-MAPKα together with a constitutively-activated upstream kinase into the hearts of rats; the hearts overexpressing p38 MAPK had increased expression of genes related to cell cycle progression and inflammation together with large areas of fibrosis. This observation, which is consistent with the established link between the p38 MAPK pathway and inflammatory responses in other organ systems, is similar to the findings in the peri-infarct region in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p38 by TAK1 induced ventricular hypertrophy [41]. Tenhunen et al [42] injected adenovirus encoding wild-type p38-MAPKα together with a constitutively-activated upstream kinase into the hearts of rats; the hearts overexpressing p38 MAPK had increased expression of genes related to cell cycle progression and inflammation together with large areas of fibrosis. This observation, which is consistent with the established link between the p38 MAPK pathway and inflammatory responses in other organ systems, is similar to the findings in the peri-infarct region in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…115 Other than fetal genes induction, several studies using gene expression profiling and detailed biochemical analysis implicated an induction of the inflammatory response and cell cycle regulation as a major consequence of constitutive p38 activation in the heart. 64,116 The induction of inflammatory cytokines can generate a positive feedback loop, leading to sustained p38 activation in the heart. 117 This observation is in agreement with the restrictive cardiomyopathy phenotype found in the p38-activated transgenic mouse heart, including extensive interstitial remodeling and stiffening of myocardium without chamber hypertrophy or dilatation.…”
Section: P38 Map Kinase In Hypertrophymentioning
confidence: 99%
“…7,[18][19][20] Recent studies have also shown that p38MAPK plays a key role in CM proliferation in both developing fetal and postnatal myocardium. 19,[21][22][23] Therefore, the purpose of the present study was to elucidate the factors that regulate the proliferation activity of immature CMs within an in vitro-engineered cardiac tissue construct independent of the non-CM population proliferation activity. We tested the hypothesis that cyclic mechanical stretch increases specifically CM proliferation within EEECT and the inhibition of p38MAPK activity decreases CM proliferation.…”
Section: Introductionmentioning
confidence: 99%